Difference between financial intelligence on millennials, gen x, and baby boomers - Njo Anastasia; Oka Christian Setiadiwiria; Yohanes Sondang Kunto (BISMA (Bisnis dan Manajemen), 2019)
The financial management of each individual depends on his financial intelligent. This study aims to examine the differences between financial knowledge and financial behavior, which are a combination of financial intelligent in each generation, namely the millennials, Gen X, and baby boomers. The sample used consisted of 100 respondents in each generation, selected using purposive sampling technique. Data collection used questionnaires distributed by online and hardcopy, which is then processed to test the differences using the ANOVA test. The results of the analysis showed that there are significant differences in financial intelligence on millennials, Gen X, and baby boomers. However, there were no difference in financial intelligence between millennials and Gen X. This proves that differences in generations that have different growth periods will have different levels of financial knowledge, resulting in differences in financial behavior. KeywordsFinancial intelligence; financial knowledge; financial behavior; millennials; Gen X; baby boomers